Dying Too Young : Addressing Premature Mortality and Ill Health Due to Non-Communicable Diseases and Injuries in the Russian Federation - World Bank (Washington, DC, 2012)
The poor health status of Russia's economically active adult population-its human capital-is imperiling sustainable economic and social development. What factors contribute to the excessive mortality, ill health, and disability in Russia, particularly among working-age adults? What are the demographic, social, and economic consequences of this phenomenon? Most importantly, what can be done to reduce these burdens? This report shows that non-communicable diseases (NCDs) and injuries are the leading causes of death, illness, and disability in Russia, and assesses the factors associated with the onset of these conditions, the demographic, financial, and economic consequences of NCDs and injuries; summarizes relevant evidence and emerging lessons from international experience, proposes a comprehensive program for addressing this problem; and projects the health and economic gains that could result from such a program.